Isoenzymatic activity in wheat plants infected by virus SBWMV - de Souza, Rocheli; Schons, Jurema; Brammer, Sandra Patussi; Prestes, Ariano Moraes; Scheeren, Pedro Luiz; e Silva, Marcio Só; Del Duca, Leo de Jesus Antunes (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> The aim of this work was to elucidate the effect of the Soil-borne wheat mosaic virus (SBWMV) on the activity and on the isoenzymatic expression of esterases, peroxidases, and aspartate aminotranferases in wheat plants. Biochemical analyses were carried out for four cultivars and one line of wheat, 45 days after emergence with different levels of resistance to SBWMV: BRS Guabiju, BRS 194, BRS 179, BR 23 and PF 980524. In general, intra and interpopulation differences in quality and quantity were detected, when comparing plants with and without symptoms of SBWMV. Nine band patterns were determined in both situations for esterase. To peroxidase and aspartato aminotransferase, three band patterns were detected for both conditions. Eletrophoretic patterns of SBWMV infected plants were observed, when compared with noninfected ones, notably for esterase, which provides a more precise identification of cell metabolic condition.